(untitled) (Cadernos de Linguagem e Sociedade, 2010)
This paper is about texts produced in an adult literacy course promoted by the Paranoá Community Centre (see Magalhães, in this number). The paper discusses literacy social practices and events in this community, as well as the political commitment of the group, the access to community life, to institutions and power. Thus, the texts show the construction of social and political identity in the group.